Cilia signaling and obesity. (February 2021) - Engle, Staci E.; Bansal, Ruchi; Antonellis, Patrick J.; Berbari, Nicolas F.
Abstract: An emerging number of rare genetic disorders termed ciliopathies are associated with pediatric obesity. It is becoming clear that the mechanisms associated with cilia dysfunction and obesity in these syndromes are complex. In addition to ciliopathic syndromic forms of obesity, several cilia-associated signaling gene mutations also lead to morbid obesity. While cilia have critical and diverse functions in energy homeostasis including their roles in centrally mediated food intake as well as in peripheral tissues, many questions remain. Here, we briefly discuss the syndromic ciliopathies and monoallelic cilia signaling gene mutations associated with obesity. We also describe potential ways cilia may be involved in common obesity. We discuss how neuronal cilia impact food intake potentially through leptin signaling and changes in ciliary G protein-coupled receptor (GPCR) signaling. We highlight several recent studies that have implicated the potential for cilia in peripheral tissues such as adipose and the pancreas to contribute to metabolic dysfunction. Then we discuss the potential for cilia to impact energy homeostasis through their roles in both development and adult tissue homeostasis. The studies discussed in this review highlight how a comprehensive understanding of the requirement of cilia for the regulation of diverse biological functions will contribute to our understanding of common forms of obesity.